Dissemination and Development of Theatre Based on New Media Context: An Example of Integration of Theatre Elements into Film - Ding, Qiuyong (Transactions on Social Science, Education and Humanities Research, 2024)
With the continuous development of modern media technology, traditional theatre art, which has long been in stagnation, has also been allowed to harmonise with modern advanced media technology and convenient media communication technology in various ways to seek a more permanent development. The relationship between theatre and film is one of the things that many scholars have explored and experimented with in this attempt to reform the theatre. With this in mind, this paper explores the current state of theatre and some of the possibilities for ways of combining theatre and film. Through the summary and analysis of previous generations' cutting-edge improvement of traditional theatre to adapt to modern development, the commonalities between the two are searched for and in this way attempts to promote the combination and development of theatre and film. The traditional form of theatre expression is no longer applicable to the current explosive growth of information into the public gaze of society, in line with the trend of the new era, the human history of theatre cultural treasures into the feasibility of innovative practices, so that the theatre exists in all kinds of emerging means of artistic expression, reflecting the results of the combination of cinema and theatre and the significance of innovative theatre reform.